2009
DOI: 10.4161/cbt.8.13.8728
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis by tea polyphenols mediated through mitochondrial cell death pathway in mouse skin tumors

Abstract: Many naturally occurring phytochemicals have shown cancer chemopreventive potential in a variety of bioassay systems. One such naturally occurring biologically active compound is tea Camellia sinensis, which is the most consumed beverage in the world after water. The most abundant and active constituents of tea are polyphenols (epigallocatechin gallate and theaflavins). In the present study, cancer chemopreventive properties of both black tea polyphenols (BTP) and green tea polyphenols (GTP) on 7,12-dimethylbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…Under the stimulation of apoptosis involving mitochondria, survivin can form a complex with XIAP, elevate the stability of XIAP and its inhibitory activity against caspases [15,16]. Common cancer treatments currently induce apoptosis by downregulating the expression of survivin [17].…”
Section: Introductionmentioning
confidence: 99%
“…Under the stimulation of apoptosis involving mitochondria, survivin can form a complex with XIAP, elevate the stability of XIAP and its inhibitory activity against caspases [15,16]. Common cancer treatments currently induce apoptosis by downregulating the expression of survivin [17].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have observed a reduction in skin tumor incidence in mice treated with black tea polyphenols potentially via induction of apoptosis [6, 7]. Research in mice, human keratinocytes, and humans also indicates a protective role forepigallocatechin-3-gallate, a catechin in green tea, in skin cancer through several possible pathways, including antioxidant activity, anti-inflammatory effects, and cutaneous photoprotection [813].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, under identical conditions, EGCg suppressed Bcl-xL mRNA expression in non-small-cell lung cancer A549 cells [48]. Bcl-xL, a member of the Bcl-2 family, inhibits apoptosis by blocking the mitochondrial cytochrome c release [49,50]. A decrease in Bcl-xL gene expression may lead to the promotion of cell death.…”
Section: Proposed Mechanism Of the Anti-cancer Effects (Experimental mentioning
confidence: 99%